Knowledge, attitudes, and practices related to hypertension among Sri Lankans: an online cross-sectional survey - Ranasinghe, Priyanga; Weerasekara, Pumudu; Manchanayake, Minura; Liyanage, Sandamini; Perera, Thilina; Silva, Minollie; Webb, David J. (BMC public health, 2025)
Background Hypertension (HTN) is a major public health issue in Sri Lanka, influenced by genetic predisposition and lifestyle factors. Despite high general literacy, gaps in health literacy and suboptimal HTN management persist. Understanding knowledge, attitudes, and practices (KAP) in HTN is crucial for developing targeted public health interventions to improve awareness and management. Methods A cross-sectional online survey was conducted among Sri Lankan adults from February to September 2024. Participants were recruited via social media, and data were collected using a structured questionnaire assessing socio-demographic characteristics, knowledge of HTN, attitudes toward prevention and treatment, and health-related practices. Knowledge scores were analysed using descriptive statistics, chi-square tests, ANOVA, and regression models. Results A total of 2,013 participants were included, with 47% diagnosed with HTN. The mean knowledge score was 57 ± 20%, with 36% of respondents scoring below 50%. Awareness of risk factors varied—while 78% recognized excessive salt intake, only 40% identified alcohol consumption as a risk factor. Knowledge of HTN consequences was uneven; 87% identified heart disease, but only 31% recognized eye disease as a complication. Urban residents and those with higher education and income had significantly better knowledge scores, while misconceptions about HTN, such as water intake being a risk factor (21%), were prevalent. Attitudes toward HTN management were generally positive, with 81% recognizing the importance of treatment adherence, though only 48% acknowledged weight loss as a preventive measure. Regular blood pressure monitoring was reported by 81%, with individuals diagnosed with HTN being 7.3 times more likely to check their BP regularly (OR: 7.28, 95% CI: 4.67–11.35, p < 0.001). Salt reduction practices were influenced by socioeconomic factors, with urban residents being 2.2 times more likely to add salt (OR: 2.21, 95% CI: 1.56–3.12, p < 0.001). Conclusion Despite Sri Lanka’s high general literacy, significant gaps exist in HTN knowledge and practices. Public health strategies should focus on improving health literacy, addressing misconceptions, and promoting behavioural change through targeted interventions, particularly among socioeconomically disadvantaged populations.